PENGARUH MEDIA BIG BOOK TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS II DI SD NEGERI 30 PALEMBANG - Putri Maharani; Liza Murniviyanty; David Budi Irawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of big book media on reading comprehension skills of grade II students at SD Negeri 30 Palembang. The method used is True Experimental Design with the type of Pretest-Posttest Control Group Design. The sample in this study were grade II B students as the experimental class and grade II D as the control class, each totaling 28 people. Data collection techniques used observation, tests and documentation, with instruments in the form of multiple choice questions. Data analysis techniques used include normality tests, homogeneity tests, and hypothesis tests. The results showed that the average data value of the experimental class pretest was 55.36, the average posttest value of the experimental class was 75.00, while the average pretest value of the control was 52.50, and the average posttest value of the control was 55.36. The output of the normality test shows that the pretest-posttest data of the control class and the pretest-posttest of the experimental class are normally distributed, with a significance value of the pretest of the control class of 0.200> 0.05 and the posttest of the control class of 0.129> 0.05, while the pretest data of the experimental class is 0.196> 0.05 and the posttest of the experimental class is 0.200> 0.05. The results of the hypothesis test using the t-test obtained a significance value of 0.000 <0.05, which means that there is a significant influence of the influence of big book media on the reading ability of class II students at SD Negeri 30 Palembang